Merry Christmas, Amelia Bedelia - Parish, Peggy; Sweat, Lynn (New York : Greenwillow Books, 1986)
As Amelia Bedelia helps Mrs. Rogers prepare for Christmas, she bakes a date cake with a calendar in it and stuffs the children$1 (Bs stockings with turkey stuffing.s
Keywords: Christmas -- Fiction; Humorous stories